Blebbistatin Inhibits Neomycin-Induced Apoptosis in Hair Cell-Like HEI-OC-1 Cells and in Cochlear Hair Cells - Gao, Song; Cheng, Cheng; Wang, Maohua; Jiang, Pei; Zhang, Liyan; Wang, Ya; Wu, Huihui; Zeng, Xuanfu; Wang, Hui; Gao, Xia; Ma, Yongming; Chai, Renjie (Frontiers in Cellular Neuroscience, 2020)
Aging, noise, and ototoxic drug-induced hair cell (HC) loss are the major causes of sensorineural hearing loss. Aminoglycoside antibiotics are commonly used in the clinic, but these often have ototoxic side effects due to the accumulation of oxygen-free radicals and the subsequent induction of HC apoptosis. Blebbistatin is a myosin II inhibitor that regulates microtubule assembly and myosin–actin interactions, and most research has focused on its ability to modulate cardiac or urinary bladder contractility. By regulating the cytoskeletal structure and reducing the accumulation of reactive oxygen species (ROS), blebbistatin can prevent apoptosis in many different types of cells. However, there are no reports on the effect of blebbistatin in HC apoptosis. In this study, we found that the presence of blebbistatin significantly inhibited neomycin-induced apoptosis in HC-like HEI-OC-1 cells. We also found that blebbistatin treatment significantly increased the mitochondrial membrane potential (MMP), decreased ROS accumulation, and inhibited pro-apoptotic gene expression in both HC-like HEI-OC-1 cells and explant-cultured cochlear HCs after neomycin exposure. Meanwhile, blebbistatin can protect the synaptic connections between HCs and cochlear spiral ganglion neurons. This study showed that blebbistatin could maintain mitochondrial function and reduce the ROS level and thus could maintain the viability of HCs after neomycin exposure and the neural function in the inner ear, suggesting that blebbistatin has potential clinic application in protecting against ototoxic drug-induced HC loss.